(untitled) (Academicia Globe: Inderscience Research, 2024)
Teacher professional development plays a key role in improving the quality of education and the success of students. The Cambridge education system provides a wide range of opportunities for teachers to improve their skills, gain new knowledge and enrich their teaching experience. One of the key features of the Cambridge education system is the emphasis on the continuous professional development of teachers.